On-chip graphene photodetectors with a nonvolatile p–i–n homojunction - Ruijuan Tian; Yong Zhang; Yingke Ji; Chen Li; Xianghu Wu; Jianguo Wang; Shuaiwei Jia; Liang Liu; Mingwen Zhang; Yu Zhang; Qiao Zhang; Zhuang Xie; et al. (Light: Science & Applications)
Abstract Graphene’s unique photothermoelectric (PTE) effect, combined with its compatibility for on-chip fabrication, promises its development in chip-integrated photodetectors with ultralow dark-current and ultrafast speed. Previous designs of on-chip graphene photodetectors required external electrical biases or gate voltages to separate photocarriers, leading to increased power consumption and complex circuitry. Here, we demonstrate a nonvolatile graphene p– i– n homojunction constructed on a silicon photonic crystal waveguide, which facilitates PTE-based photodetection without the need for electrical bias or gate voltages. By designing an air-slotted photonic crystal waveguide as two individual silicon back gates and employing ferroelectric dielectrics with remnant polarization fields, the nonvolatile p–i–n homojunction with a clear gradient of Seebeck coefficient is electrically configured. Hot carriers in the graphene channel generated from the absorption of waveguide evanescent field are separated by the nonvolatile p– i– n homojunction effectively to yield considerable photocurrents. With zero-bias and zero-gate voltage, the nonvolatile graphene p–i–n homojunction photodetector integrated on the optical waveguide exhibits high and flat responsivity of 193 mA W−1 over the broadband wavelength range of 1560–1630 nm and an ultrafast dynamics bandwidth of 17 GHz measured in the limits of our instruments. With the high-performance on-chip photodetection, the nonvolatile graphene homojunction directly constructed on silicon photonic circuits promises the extended on-chip functions of the optoelectronic synapse, in-memory sensing and computing, and neuromorphic computing.